2021
DOI: 10.1186/s12864-021-08115-x
|View full text |Cite|
|
Sign up to set email alerts
|

Testing assembly strategies of Francisella tularensis genomes to infer an evolutionary conservation analysis of genomic structures

Abstract: Background We benchmarked sequencing technology and assembly strategies for short-read, long-read, and hybrid assemblers in respect to correctness, contiguity, and completeness of assemblies in genomes of Francisella tularensis. Benchmarking allowed in-depth analyses of genomic structures of the Francisella pathogenicity islands and insertion sequences. Five major high-throughput sequencing technologies were applied, including next-generation “short-read” and third-generation “long-read” sequen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 148 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…Any correlation between sequencing depth or evenness with assembly quality in plastid genomes may, therefore, be compounded by the idiosyncrasies of specific NGS platforms and assembly software tools. Given that most NGS sequencing platforms exhibit idiosyncratic error rates between 0.1% and 1% of the generated nucleotides Fox et al [33], a non-trivial number of the sequence reads underlying a genome assembly may represent erroneous data, possibly causing a distinct variation in sequencing depth or evenness [11,34]. Similarly, many of the various software tools for de novo plastid genome assembly [35,36] cannot assemble a complete plastid genome directly, but generate long sequence contigs that must still be post-processed and concatenated to obtain a complete plastome assembly [37].…”
Section: Introductionmentioning
confidence: 99%
“…Any correlation between sequencing depth or evenness with assembly quality in plastid genomes may, therefore, be compounded by the idiosyncrasies of specific NGS platforms and assembly software tools. Given that most NGS sequencing platforms exhibit idiosyncratic error rates between 0.1% and 1% of the generated nucleotides Fox et al [33], a non-trivial number of the sequence reads underlying a genome assembly may represent erroneous data, possibly causing a distinct variation in sequencing depth or evenness [11,34]. Similarly, many of the various software tools for de novo plastid genome assembly [35,36] cannot assemble a complete plastid genome directly, but generate long sequence contigs that must still be post-processed and concatenated to obtain a complete plastome assembly [37].…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], it was reported that Röbbe Wünschiers’ name was misspelled as Roebbe Wuenschiers.…”
mentioning
confidence: 99%